World commodity outlook 1977/78 : industrial raw materials - Economist Intelligence Unit (Great Britain) (London : Economist Intelligence Unit, 1977)
The outlook covers industrial raw materials including Abaca, Aluminium, Antimony, Castor oil, Chrome, Copper, Cotton, Hides, Iron ore, Jute, Lead, Linseed, Manganese, Molybdenum, Nickel, Rubber, Sissal, Silver, Tin, Timber, Tung oil, Tungsten, Wool and Zinc
osc 10/12/2019
Loans
Keywords: Industry and trade; Industrial raw materia; Industry; Business forecasting